The Influence of Net Working Capital and Sales Growth on Company Financial Performance (A Study of Banking Companies Listed on the Indonesia Stock Exchange 2018–2022) - Lia Nurjanah; Intan Pramesti Dewi (Universitas KH. Abdul Chalim Mojokerto, 2025)
A company's financial performance reflects the outcomes of various activities that contribute to its overall success. This study investigates the impact of net working capital and sales growth on financial performance, both jointly and individually. A quantitative approach is applied, utilizing secondary data and EViews version 12 to test the research hypotheses. The analysis includes multicollinearity testing, heteroscedasticity testing, Chow test, Hausman test, Lagrange multiplier test, and the common effect model. The results indicate that net working capital and sales growth, when considered together, have a significant and positive effect on financial performance.